Effectiveness of Music on Quality of Sleep in Elderly: An Narative Review - Chrisnawati Chrisnawati; Anastasia Maratning; Dyah Trifianingsih; Tri Jaya Firmansyah (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2022)
Sleep-wake disorders in the elderly cause poor sleep quality, contribute to worsening disease conditions, increase fatigue and weakness, increase the risk of falls and cause injury. Music, one of the relaxation techniques, helps improve sleep quality because it is accessible. This study aims to determine the effectiveness of music on sleep quality in the elderly. This research is a simple narrative literature review conducted using conceptual analysis techniques. Articles were selected through the PRISMA chart with the criteria; article related to music intervention on sleep quality in the elderly, 2010-2020 publication, design: pre-experimental type, quasi-experimental and RCT. A total of 13 articles were obtained from the ScienceDirect, PubMed, and GoogleScholar databases. Seeing the effect of music intervention actions such as sessions, duration, and duration of giving, music with soft characteristics can improve the sleep quality of the elderly. The choice of music must be considered as a way to achieve maximum relaxed conditions. Music facilitates a state of relaxation, making the elderly gets more efficient and easier to fall asleep. Music with soft characteristics can improve sleep quality and is recommended as an alternative to improve the sleep quality of the elderly.